2014
DOI: 10.1016/j.febslet.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of phospholipid scramblases

Abstract: Phospholipid scramblase activity is involved in the collapse of phospholipid (PL) asymmetry at the plasma membrane leading to externalization of phosphatidylserine. This activity is crucial for initiation of the blood coagulation cascade and for recognition/elimination of apoptotic cells by macrophages. Efforts to identify gene products associated with this activity led to the characterization of PL scramblase (PLSCR) and XKR family members which contribute to phosphatidylserine exposure in response to apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 152 publications
0
79
0
Order By: Relevance
“…Apoptosis goes along with phospholipid scrambling and PtdSer exposition [14] and TMEM16F, among others, functions as a phospholipid scramblase [4,26]. Thus Annexin V-FITC staining was employed to test if TMEM16F KD altered the amount of PtdSer exposed on the external leaflet of the plasma membrane.…”
Section: Inducible Knockdown Of Tmem16f Led To Attenuated Growth Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis goes along with phospholipid scrambling and PtdSer exposition [14] and TMEM16F, among others, functions as a phospholipid scramblase [4,26]. Thus Annexin V-FITC staining was employed to test if TMEM16F KD altered the amount of PtdSer exposed on the external leaflet of the plasma membrane.…”
Section: Inducible Knockdown Of Tmem16f Led To Attenuated Growth Of Hmentioning
confidence: 99%
“…Phospholipid scrambling by TMEM16F can occur during apoptosis or upon cell activation [7,14,15]. This effect is essential during platelet activation and bone mineralization by osteoblasts [1,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The lipid bilayer shows a bent shape and contains a concave region in the annexin-membrane interaction interface, which supports the idea that ANX V could disturb the stability of lipids and bend membranes [66]. Cell injury leads to redistribution of lipids within the plasma membrane resulting in surface exposure of PS and phosphatidylethanolamine (PE) [67] and phospholipid scramblase activity produces a collapse of phospholipid asymmetry with externalization of PS [68]. The physiological functions known for externalized PS are: (1) control of the hemostatic balance, since several pro-coagulant as well as anticoagulant reactions require PS-containing lipid surfaces [69], and (2) mediating recognition and clearance of apoptotic cells by phagocytic cells, to prevent release of the inflammatory cell content upon cell lysis [70].…”
Section: Understanding the Use Of Annexin V In Sperm Selectionmentioning
confidence: 56%
“…Moreover, the induction of PLSCR1 transcription depends upon sequential activation of protein kinase C delta (PKC), c-Jun N-terminal kinases, and the phosphorylation of STAT1 at Ser-727 [99]. PLSCR1 was also shown to interact with several protein kinases including c-Abl, c-Src, PKC and onzin, suggesting a role of PLSCR1 in cell signaling [100][101][102]. Employinging an inducible PLSCR1-expressing myeloid leukemia U937 cell line, we showed that inducible PLSCR1 expression arrests the proliferation at the G 1 phase and induces granulocyte-like differentiation with increased sensitivity to etoposide-induced apoptosis of the genetically engineered cells [103].…”
Section: Wogonin and Wogonosidementioning
confidence: 99%